Material Behavior Under Dynamic Mono- and Biaxial Loading - MEYER, L. W.; HERZIG, N.; PURSCHE, F.; ABDEL-MALEK, S. (Engineering Transactions, 2010)
This paper gives an overview of different testing methods and the mechanical material behavior including mono-axial and multi-axial testing under high rate loading. Special emphasis is laid on difficult loading conditions and loading states such as a high temperature and high strain loading (ϑ > 1200°C, φ > 1) and multiaxial impact tests. The impact behavior of selected materials is shown and compared for different loading conditions. Furthermore, a distinction is made between virgin and manufactured material behavior (e.g. welding) or pre-damaged materials. Specifically, if the influence of the manufacturing history is investigated. Under certain loading states the impact material properties show a dramatic difference compared to the virgin state of the material. Some examples of different material behavior under the conditions previously mentioned are given.